How Does “SPEAKING” Work in Pesantren?: An Ethnography of Arabic Communication Based on Dell Hymes' Framework - Muhammad Zaky Sya'bani; Sembodo Ardi Widodo; Sunarwoto (UIN Syekh Wasil Kediri, Indonesia, 2026)
Arabic language learning in pesantren faces a paradox between the demands of active participation of students and a communication structure that emphasizes hierarchy, obedience, and ta'zim to ustadz. This study aims to analyze the communication model of Arabic language learning at the Al Muhsin Islamic Boarding School Metro Lampung using the communication ethnographic approach and the Dell Hymes SPEAKING framework. The study used a qualitative design with data collected over three months through participant observation of 12 learning activities and 8 informal interactions, recording of six 75-minute communication events, in-depth interviews with five informants, and documentation. Data are analyzed through condensation, presentation and verification of conclusions. The results of the study show that Arabic language learning communication takes place in a participatory-controlled communication pattern based on adab. Ustadz still has linguistic and epistemic authority in determining the material, the turn of speaking, the choice of code and the accuracy of the answers, while the students gain space to imitate, ask questions, dialogue, translate and help their peers. Arabic is positioned as the language of knowledge, religion and identity of Islamic boarding schools, while code transfer to Indonesian functions as pedagogical scaffolding, a means of collaboration and comprehension support. The norm of waiting for the turn of the speaker functions as a class management as well as strengthening the manners and authority of the ustaz. Theoretically, these findings extend the use of the SPEAKING framework from simply mapping the elements of communication to an instrument for uncovering language ideologies, power relations, epistemic authority and negotiations between obedience and participation in traditional religious institutions. This study concludes that learning Arabic in Islamic boarding schools can develop the active participation of students without eliminating hierarchy and adab values, if the authority of the ustadz is accompanied by a space for dialogue, peer assistance, pedagogical code transfer, and contextual communication practices. Abstrak Pembelajaran bahasa Arab di pesantren menghadapi paradoks antara tuntutan partisipasi aktif santri dan struktur komunikasi yang menekankan hierarki, kepatuhan, serta ta’zim kepada ustadz. Penelitian ini bertujuan menganalisis model komunikasi pembelajaran bahasa Arab di Pondok Pesantren Al Muhsin Metro Lampung menggunakan pendekatan etnografi komunikasi dan kerangka SPEAKING Dell Hymes. Penelitian menggunakan desain kualitatif dengan data yang dikumpulkan selama tiga bulan melalui observasi partisipan terhadap 12 kegiatan pembelajaran dan 8 interaksi informal, perekaman enam peristiwa komunikasi berdurasi 75 menit, wawancara mendalam terhadap lima informan, serta dokumentasi. Data dianalisis melalui kondensasi, penyajian dan verifikasi kesimpulan. Hasil penelitian menunjukkan bahwa komunikasi pembelajaran bahasa Arab berlangsung dalam pola komunikasi partisipatif-terkendali berbasis adab. Ustadz tetap memiliki otoritas linguistik dan epistemik dalam menentukan materi, giliran berbicara, pilihan kode dan ketepatan jawaban, sementara santri memperoleh ruang untuk menirukan, bertanya, berdialog, menerjemahkan dan membantu teman sebaya. Bahasa Arab diposisikan sebagai bahasa ilmu, agama dan identitas pesantren, sedangkan alih kode ke bahasa Indonesia berfungsi sebagai pedagogical scaffolding, sarana kolaborasi dan dukungan pemahaman. Norma menunggu giliran berbicara berfungsi sebagai manajemen kelas sekaligus penguatan adab dan otoritas ustadz. Secara teoretis, temuan ini memperluas penggunaan kerangka SPEAKING dari sekadar pemetaan unsur komunikasi menjadi instrumen untuk mengungkap ideologi bahasa, relasi kuasa, otoritas epistemik dan negosiasi antara kepatuhan dan partisipasi dalam institusi keagamaan tradisional. Penelitian ini menyimpulkan bahwa pembelajaran bahasa Arab di pesantren dapat mengembangkan partisipasi aktif santri tanpa menghilangkan hierarki dan nilai adab, selama otoritas ustadz disertai ruang dialog, bantuan teman sebaya, alih kode pedagogis, dan praktik komunikasi yang kontekstual.